Marketing Strategy of Jaring Acil Baluh Products in Pingaran Village, Astambul District - Inayatul Khadijah; Jumriani Jumriani; M. Ridha Ilhami; Fatwa Nur'aini; Syarifuddin Syarifuddin (Universitas Lambung Mangkurat, 2026)
Jaring Acil Baluh products are processed foods that are commonly found in Pingaran Village, Astambul District, which are known for their unique blend of Jaring flavors and Tahilala sauce based on hereditary recipes. Although it has advantages in terms of taste and cultural value, this business still faces various challenges in its marketing strategy which is carried out conventionally, especially in the aspects of packaging, promotion, and distribution which limit market reach. This study aims to describe the marketing strategy applied by the Jaring Acil Baluh production house through a descriptive qualitative method with observation, interview, and documentation techniques, as well as data analysis which includes data reduction, presentation, and verification through triangulation. The results showed that the marketing strategy of this business includes four main aspects, namely products with distinctive flavors and simple packaging, pricing based on the size and quality of Jaring, distribution through production houses and two branch stalls on the strategic route of Jalan A. Yani, and promotions carried out directly to consumers without utilizing digital media, as a form of adaptation in maintaining business sustainability in the midst of limited resources.